Implementation of Blended Learning to Improve Critical Thinking Skills and Motivation - Dwiastuti, Sri; Widoretno, Sri; Ramli, Murni; Prabowo, Chandra Adi (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
The aims of this research are to 1) know the differences of Critical Thinking Skills from blended learning in Diversity dan Classification of Invertebrate course, 2) find out the result of the blended learning implementation concerning study motivation in Diversity dan Classification of Invertebrate course at Biology Education program, 3) know the effect of blended learning on critical thinking in solving problems. Blended learning-based learning is a combination of face-to-face and online learning. Online learning is learning through various learning facilities such as using material sharing via PowerPoint, WAG, email, recitation of downloading material from various journals without the need for a face-to-face meeting. The research subject were students of the second-semester Biology education program. Data collection on critical thinking skills was taken from test scores after learning eight times, learning motivation data was taken through a questionnaire. Different test analyses using One Way ANOVA with a prerequisite test consist of normality test (Saphiro-Wilk Test) and homogeneity with Levene Test. The questionnaire analysis uses Rasch analysis with the help of Winsteps version 4.6. From the results of the study, it can be concluded that 1) there is a significant difference in critical thinking skills in blended learning and online learning, 2) there is a difference in learning motivation from blended learning and online learning, 3) there is a positive effect on critical thinking skills in solving problems given in blended learning